Effect of integrated fertilizer and plant density management on yield, root characteristic and photosynthetic parameters in maize on the semiarid Loess Plateau - Wang, Shuying; Zhao, Gang; Ma, Mingsheng; Lei, Kangning; Li, Shangzhong; Cheng, Wanli; Dang, Yi; Wang, Lei; Zhang, Jianjun; Zhou, Gang; Li, Xingmao; Ni, Shengli (Frontiers in Agronomy, 2024)
IntroductionImproving photosynthetic use efficiency in dryland agroecosystems to sustain high agricultural yields is a key responsibility for ensuring food security.MethodsThis study was conducted in the regions on the semiarid Loess Plateau of China during 2018–2020. Dryland maize of Xianyu 335 comprised four modes: basic yield input (CK, plastic film mulching, 37500 plant.ha-1 of plant density and unfertilized), farmer input (FP, plastic film mulching, 45000 plant.ha-1 of plant density and inorganic nitrogen(N) and phosphate(P) fertilizer were 150kg.ha-1 and 90kg.ha-1), high yield and high-efficiency input (HH, full plastic-film mulching on double furrow, 67500 plant.ha-1 of plant density and N, P and organic manure(M) fertilizer were 230kg.ha-1, 140kg.ha-1 and 1500kg.ha-1), and super high yield input (SH, full plastic-film mulching on double furrow, 9000 plant.ha-1 of plant density and N, P and organic M fertilizer were 300kg.ha-1, 180kg.ha-1 and 7500kg.ha-1). The effects of different cultivation modes on yield, WUE, net photosynthetic rate(Pn), leaf area index(LAI), chlorophyll index(SPAD value) and root index were studied.ResultsThe results showed that the value average of yield and WUE for CK were 7790kg and 17480kg.ha-1 in three years. SH, HH and FP cultivation modes of yield and WUE was significant higher compared with CK cultivation mode (P<0.05). SH, HH and FP cultivation modes of yield and WUE increased by 34.01%, 48.68%, 56.39% and 34.34%, 47.99%, 57.99%, compared than CK cultivation mode. These differences were observed during the seedling stage, jointing stage, silking stage and filling stage. Year to year variation in performance of applied treatment, this improved in CK cultivation mode significantly enhanced SPAD value, Pn, LAI and the root index than SH, HH and FP cultivation modes. The yield exhibited a positive correlation with the WUE, SPAD value, Pn, LAI. The SH cultivation mode was the highest yields.DiscussionThe results indicated that maize yield and WUE could be increased through integrating and optimizing cultivation techniques in maize production on the semiarid western Loess Plateau of China. The SH cultivation mode was the highest yields. The primary factor contributing to the increase in yield and WUE of maize due to increased density, increased fertilizer and covering measures is the augmentation of Pn, LAI, SPAD value, and root index.